"Heat shock protein 70 in pancreatic diseases: Friend or foe". Issue 1 (22nd May 2017) - Giri, Bhuwan; Sethi, Vrishketan; Modi, Shrey; Garg, Bharti; Banerjee, Sulagna; Saluja, Ashok; Dudeja, Vikas
Abstract : The heat shock response in pancreatitis that is activated via HSP70 protects acinar cells through multiple simultaneous mechanisms. It inhibits trypsinogen activation and modulates NF‐κB signaling to limit acinar cell injury. On the other hand, HSP70 is overexpressed in pancreatic cancer and is hijacked by the cellular machinery to inhibit apoptosis. Inhibition of HSP70 in pancreatic cancer by a novel compound, Minnelide, has shown considerable clinical promise.